Tumor microenvironment and noncoding RNAs as co‐drivers of epithelial–mesenchymal transition and cancer metastasis. Issue 3 (18th September 2017) - Drak Alsibai, Kinan; Meseure, Didier
Abstract : Reciprocal interactions between cancer cells and tumor microenvironment (TME) are crucial events in tumor progression and metastasis. Pervasive stromal reprogramming of TME modifies numerous cellular functions, including extracellular matrix (ECM) stiffness, inflammation, and immunity. These environmental factors allow selection of more aggressive cells that develop adaptive strategies associating plasticity and epithelial‐mesenchymal transition (EMT), stem‐like phenotype, invasion, immunosuppression, and resistance to therapies. EMT is a morphomolecular process that endows epithelial tumor cells with mesenchymal properties, including reduced adhesion and increased motility. Numerous studies have demonstrated involvement of noncoding RNAs (ncRNAs), such as miRNAs and lncRNAs, in tumor initiation, progression, and metastasis. NcRNAs regulate every hallmark of cancer and have now emerged as new players in induction and regulation of EMT. The reciprocal regulatory interactions between ncRNAs, TME components, and cancer cells increase the complexity of gene expression and protein translation in cancer. Thus, deeper understanding of molecular mechanisms controlling EMT will not only shed light on metastatic processes of cancer cells, but enhance development of new therapies targeting metastasis. In this review, we will provide recent findings on the role of known ncRNAs relevant to EMT and cancer metastasis and discuss the role of the interaction between ncRNAs and TME as co‐drivers of EMT. Developmental Dynamics 247:405–431, 2018 . © 2017 Wiley Periodicals, Inc. Key Findings: Reciprocal interactions between cancer cells and tumor microenvironment are crucial events in tumor progression and metastasis. Reciprocal interactions and/or regulations between tumor microenvironment and ncRNAs, (miRNAs and lncRNAs) play an important role in driving cancer cells plasticity and heterogeneity, resistance to therapies and metastatic spread. NcRNAs regulate every hallmark of cancer and have now emerged as new players in induction and regulation of EMT.